Prophylactic antibiotics may not be necessary for transoral endoscopic thyroidectomy - Lee, Jun Sung; Kim, Hee Jun; Lee, Jin Seok; Yun, Hyeok Jun; Lee, Suji; Cheong, Jae-Ho; Kim, Soo Young; Kim, Seok-Mo; Chang, Hojin; Lee, Yong Sang; Park, Cheong Soo; Chang, Hang-Seok (Frontiers in Surgery, 2022)
Background: With the recent advances in thyroid cancer surgery techniques and the increasing number of patients concerned about cosmetics, the use of transoral endoscopic thyroidectomy is increasing globally. The aim of this study was to determine whether transoral endoscopic thyroidectomy is truly a clean-contaminated surgery. Methods: From September 2016 to April 2018, 20 patients with thyroid cancer underwent transoral endoscopic thyroidectomy performed by a single surgeon at Gangnam Severance Hospital. Before and after surgery, the oral cavity was swabbed to obtain culture samples, and antibiotics were administered twice before surgery and once after surgery. Results: Of the total 20 patients, no bacteria were identified before or after surgery in eight (40%) patients. Bacteria were identified both before and after surgery in seven patients (35%). In four patients (20%), bacteria were not identified before surgery, but bacteria were identified after surgery. Bacteria were identified before surgery but not after surgery in one patient (5%). No complications, including surgical site infection, were observed. All the bacteria identified were normal flora of the oral cavity and skin. Conclusions: Considering the patient’s position and surgical extent in transoral endoscopic thyroidectomy, we believe it should be considered a clean surgery because it is difficult for bacteria to invade the surgical site. Further studies on transoral endoscopic thyroidectomy without the use of antibiotics are needed to confirm that prophylactic antibiotics are not required for this surgery.